Cooperative Halogen Bond, Tetrel Bond and Van Der Waals Interaction Coexisting in the CO2, CO and XY (X=Cl, Br; Y=F, Cl, Br) Trimeric Complexes. Issue 8 (17th June 2016) - Yang, Xing; Zhou, Pan‐Pan; Yang, Fan; Zhou, Da‐Gang; Yan, Chao‐Xian; Zheng, Pei‐Jun; Dai, Yang
Abstract: A series of four‐membered ring‐shaped molecular complexes formed by CO2, CO and XY (X=Cl, Br; Y=F, Cl, Br) molecules have been investigated at the moderate M06‐2X/6‐311++G(2d, 2p) level of theory, in which these molecules interact with each other via halogen bond, tetrel bond and van der Waals interaction. The optimized geometry, stretching mode and interaction energy have been obtained and discussed. Molecular electrostatic potential and the contour maps of Laplacian ∇ 2 ρ were used to reveal the formation mechanisms of these complexes. The cooperativity was found in these complexes because their interaction energies are stronger than the sum of the pair interaction energies. The electrostatic force was believed to be the main net contribution to the stability of these complexes. The simultaneous interactions involving CO2, CO and dihalogen molecules in these complexes would provide insight into the CO2 and CO fixation via noncovalent interactions. Abstract : CO2, CO and XY (X=Cl, Br; Y=F, Cl, Br) molecules can interact with each other via cooperative halogen bond, tetrel bond and van der Waals interaction, forming four‐membered ring‐shaped molecular complex with four types.